Periodicities of palaeo-climatic records extracted from the Dome Fuji deep core - Satow, Kazuhide; Watanabe, Okitsugu; Fujii, Yoshiyuki; Kamiyama, Kokichi; Motoyama, Hideaki; Furukawa, Teruo; Igarashi, Makoto; Kanamori, Satoru (National Institute of Polar Research, 2004)
P(論文) The Antarctic ice sheet preserves palaeo-climate information in the form of physical and chemical stratigraphy. A deep ice core was continuously drilled down to a depth of 2503m at Dome Fuji Station, East Dronning Maud Land, Antarctica, during the 1993-97 JARE inland operations. A time scale for the Dome Fuji core is calculated from past accumulation rates and an ice flow model. A depth-age profile was obtained for the past 320kyr back in time. The obtained palaeo-temperature profile shows the past three glacial and interglacial periods. The power spectrum for oxygen isotope variation for 320kyr shows three dominant cycles of 107kyr, 40kyr and 21kyr. Each of these three cycles is similar to Milankovitch cycles. Moving-window spectrum analysis, using a 130kyr window stepped by 10kyr over the past 320kyr, found these main cycles in every age. Variations of other chemical concentrations were also recovered from the Dome Fuji ice core, and are inversely correlated to the temperature profile. Concentrations of terrestrial and marine origin substances are high in glacial periods, and low in interglacial periods. Over the past 320kyr, the dominant periodicities of temperature were also detected in almost all chemical records. departmental bulletin paper